Resurrection of the genus Eremothyris Walsingham (Lepidoptera, Zygaenoidea, Lacturidae) - Huang, Si-Yao; Martin, Geoff; Espeland, Marianne (Zootaxa, 2024)
The African lacturid genus Eremothyris Walsingham, 1897 stat. rev. is resurrected from the synonym of Gymnogramma Zeller, 1852 based on the examination of the type species of both genera. The checklist of the genus Eremothyris is provided. The following new combinations are given: E. atmocycla (Meyrick, 1918) comb. n., E. privata (Meyrick, 1924) comb. n., E. racemosa (Meyrick, 1918) comb. n., E. sphaerobola (Meyrick, 1924) comb. n. and E. tabulatrix (Meyrick, 1930) comb. n. Adult and genitalia of the type species of the genera Eremothyris and Gymnogramma are illustrated.